Kinetic and Thermodynamic Studies of Free and Alginate/Agar-Agar Immobilized a-Amylase Catalyzed Reaction - Pramanik, Soumen; Kumar Sarwa, Khomendra; Kumar Dolui, Ashoke; Kumar, Atul (Asian Journal of Chemistry, 2013)
The present study deals with the immobilization of a-amylase into alginate and agar-agar medium and determination of kinetics as well as thermodynamic parameters of both free and immobilized enzyme catalyzed reaction to predict the extent of reaction and the position of equilibrium. At optimized condition, the Km value derived from Lineweaver Burk plot for free enzyme (0.40 % w/v) was lower than the immobilized enzyme (0.52 % w/v for alginate and 0.76 % w/v for agar-agar immobilized). The free enzyme had an Ea value of 1609 cal/mol compared to those of immobilized enzyme (6495 cal/mol for alginate and 3542 cal/mol for agar-agar immobilized). Computed DS value for free enzyme is more negative than the immobilized enzyme. The increasing value DGº in immobilized enzyme system indicates that the enzyme-substrate reaction is slower during immobilization. However immobilized enzyme could be reused even after 12 days of storage.